Art therapy as a strategy for social inclusion and educational improvement in educational contexts - López Ruiz, David (Avances en Supervisión Educativa, 2016)
Changes in the rhythm of life of people and the constant sense of anxiety or stress produced by a society that really know, can sometimes cause a vacuum that does not always know to give a clear and comfortable response. In certain cases, it is more usual to see people defend themselves from the society around them to enjoy herself. So, life in society "tries to explain how we perceive, learn, remember, solve problems, communicate, feel and relate to other people, from birth to death, in private and in groups" (Morris & Maisto 2005: 4). Working from art and use it as a tool for self-expression through their media, manages a wide range of possibilities are for educational contexts, an open window of possibilities able to achieve greater social cohesion and progress in education.